2021
DOI: 10.3389/fspor.2021.760533
|View full text |Cite
|
Sign up to set email alerts
|

Sitting for Too Long, Moving Too Little: Regular Muscle Contractions Can Reduce Muscle Stiffness During Prolonged Periods of Chair-Sitting

Abstract: In modern Western societies, sedentary behavior has become a growing health concern. There is increasing evidence that prolonged sitting periods can be associated with musculoskeletal disorders. While it is generally recognized that back muscle activity is low during chair-sitting, little is known about the consequences of minor to no muscle activity on muscle stiffness. Muscle stiffness may play an important role in musculoskeletal health. This study investigated the effects of regular muscle contractions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…However, no cause-effect relationship can be inferred from these case-control studies. To obtain information on mechanistic relationships between specific occupational workloads and LBP, previous studies have examined trunk mechanical and neuromuscular characteristics before and after work shifts [ 18 , 19 ] or simulations thereof [ 20 , 21 ]. Of particular interest was prolonged work in a flexed posture, such as seen in crane operators [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no cause-effect relationship can be inferred from these case-control studies. To obtain information on mechanistic relationships between specific occupational workloads and LBP, previous studies have examined trunk mechanical and neuromuscular characteristics before and after work shifts [ 18 , 19 ] or simulations thereof [ 20 , 21 ]. Of particular interest was prolonged work in a flexed posture, such as seen in crane operators [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported possible changes in sitting balance, trunk reflex functions, and intrinsic trunk stiffness after exposure to spinal flexion [ 20 , 21 , 23 , 24 ], providing indications for possible mechanisms underlying the development of LBP. However, apart from preliminary evidence of increased shear modulus after prolonged sitting [ 19 , 25 ], the effect of prolonged flexion and other physical workloads on intrinsic trunk muscle stiffness (shear modulus) is largely unknown. Therefore, studies to examine the changes in shear modulus after prolonged flexion and physically demanding work in general are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to implement ergonomic interventions, such as adjusting workstations, providing rest breaks, and rotating tasks, to reduce the risk of WMSDs ( 8 ). As for the factors of work posture load, sitting for long periods, working in uncomfortable posture, and performing repetitive operations were identified as risk factors for WMSDs, factors of which could lead to local muscle fatigue and increase the risk of WMSDs ( 26–29 ). Therefore, it was crucial to implement ergonomic interventions, such as adjusting workstations, providing rest breaks, and rotating tasks, to reduce the risk of WMSDs.…”
Section: Discussionmentioning
confidence: 99%
“…Since early 2020, numerous studies have stressed that low back pain and sagittal imbalance has become quite more frequent in individuals of all ages and particularly students and young workers [15 , [47] , [48] , [49] , [50] , [51] . Oftentimes, these individuals enter a vicious circle, where they seek relief from pain in sitting, but bad sitting postures only deteriorate their pain and the underlying spinal condition [52] . This is expected to increase the demand for spine surgery among younger or middle – aged individuals in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%